Assessing the Concept Understanding Abilities of Prospective Biology Teachers - Citraningrum, Mivtha; Sanjaya, Yayan; Sudargo, Fransisca; ., Riandi (KnE Social Sciences, 2024)
This study aimed to identify the levels of understanding of prospective biology teacher students on the concept of invertebrates based on the cognitive process dimensions of Bloom’s Taxonomy. The method used in this research was descriptive qualitative. This research was conducted on 15 prospective biology teacher students. The instrument used was a multiple choice concept mastery test. Based on data analysis, the average cognitive ability of students is 69.10. The acquisition of conceptual understanding based on the dimensions of cognitive processes includes C1: 74,69; C2: 73.67; C3: 57.34; C4: 56.08, and C5: 22.34. The average score of cognitive ability showed that students’ cognitive abilities were still below the criteria for completeness set in the invertebrate zoology course. Keywords: assessing, concept, understanding, abilities, prospective teachers, biology